How important is wine at an Italian festival?. Issue 2 (2nd April 2016) - Draper, Jason; Christopher Taylor, D.; de Kok, Deborah
Abstract: Festival attendees have various motivations, especially for cultural festivals which typically include numerous activities, entertainment, and other components. Planners of such festivals are challenged with what aspects of a festival they might enhance for attendees. The purpose of this study is to examine relationships between motivation for attending an Italian festival and the importance of types of and characteristics of wine at the festival. Results indicate attendees motivated by the festival culture prefer quality wine(s) reflecting the festival's culture. Attendees motivated by escape prefer other wines at a reasonable price and value. Implications for festival organizers are discussed, as well as opportunities for future research.